2009
DOI: 10.1080/00365540802651905
|View full text |Cite
|
Sign up to set email alerts
|

Nocardial infection in Crete, Greece: Review of fifteen cases from 2003 to 2007

Abstract: During a 5-y period (2003 - 2007), nocardial infections were diagnosed in 15 patients admitted to the University Hospital of Heraklion, Crete, Greece. Nine patients (60%) had 1 or more underlying conditions predisposing to nocardiosis. The skin was involved in 10 cases, followed by the lung in 4. One patient had disseminated disease. Five different species were identified: N. brasiliensis (n =7), N. otitidiscaviarum (n=4), N. abscessus (n=2), N. transvalensis (n=1), and N. farcinica (n=1). The most common spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…However, antimicrobial susceptibility patterns differ widely among Nocardia species 10 22. Multiple small studies have compared the susceptibility profile of N. abscessus to other Nocardia species 16 19–21 23 24. These have shown that N. abscessus is usually sensitive to TMP/SMX,19–21 though resistant isolates of N. abscessus have been reported 25.…”
Section: Discussionmentioning
confidence: 99%
“…However, antimicrobial susceptibility patterns differ widely among Nocardia species 10 22. Multiple small studies have compared the susceptibility profile of N. abscessus to other Nocardia species 16 19–21 23 24. These have shown that N. abscessus is usually sensitive to TMP/SMX,19–21 though resistant isolates of N. abscessus have been reported 25.…”
Section: Discussionmentioning
confidence: 99%
“…abscessus infection is thought to be rare in humans. N. abscessus infection is the cause of 15-18% of nocardiosis cases [7][8][9]. In a retrospective study over 7 years (1997-2003) including 27 clinical isolates of Nocardia spp., 6 (22%) were identified as N. abscessus [10].…”
Section: Discussionmentioning
confidence: 99%
“…Nokardiya tedavisinde kullanı-lan trimetoprim-sülfametoksazol, minosiklin, üçüncü kuşak sefalosporinler ve kinolonlar gibi antibiyotiklere karşı giderek artan direnç oranları, nokardiya tedavisinde tigesiklin ve linezolid gibi yeni antibiyotiklerin kullanımını gündeme getirmiştir. Ayrıca nokardiya izolatlarının kullanılan bu yeni antibiyotiklere duyarlı olduğu gösterilmiştir (18). İmmünsupresyonu, yaygın hastalığı veya santral sinir sistemi tutulumu olan hastalar ve ciddi olgularda kombinasyon tedavisi önerilmektedir (19,20).…”
Section: şEkil 4a Ve B: Etrafı Nekroz Alanları Ve Inflamatuar Hücreleunclassified